Peran Gender dalam Kegiatan Pertanian di Nagari Api-Api Pasar Baru Kabupaten Pesisir Selatan, Sumatera Barat - Yurike, Yurike; Yudha Saktian Syafruddin (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
The agricultural sector in Indonesia plays an important role in the economy, but there is still significant gender inequality in women's access and participation. This study was conducted in Nagari Api-Api Pasar Baru, Bayang District, Pesisir Selatan Regency, West Sumatra. This study aims to analyze the roles of men and women in agriculture and the factors causing gender inequality. The study used a qualitative approach with Harvard model gender analysis. Primary data were obtained through interviews, while secondary data were taken from related agencies and literature. The results of the study show that men's roles are more dominant in agricultural work that requires physical labor, while women more often work as farm laborers with lower wages and limited involvement in decision-making. Although the Minangkabau customary system places land ownership in the hands of women, its management is still dominated by men. The low level of education of women also limits their access to agricultural resources, technology, and training. Differences in wages and workloads show significant gender bias. Cultural factors and gender stereotypes reinforce this inequality, hindering women's opportunities in the agricultural sector. Therefore, more inclusive policies are needed to improve women's access to resources and equal opportunities in decision-making, training, education, and agricultural technology to reduce gender gaps and improve the welfare of female farmers.